Activity of quinolones in the Ames Salmonella TA102 mutagenicity test and other bacterial genotoxicity assays. - Mamber, S W (1993)
Eight quinolones were examined for their bacterial mutagenicity in the Ames Salmonella TA102 assay and for their effects in other bacterial genotoxicity assays. In the quantitative Ames plate incorporation assay, all eight quinolones induced His+ deletion reversion in Salmonella tester strain TA102, with maximum reversion observed at about two to eight times the MIC. The quinolones also induced the SOS response. At quinolone concentrations close to the MIC, SOS cell filamentation gene sulA was induced in sulA::lacZ fusion strain Escherichia coli PQ37. RecA-mediated cleavage of lambda repressor in lambda::lacZ fusion strain E. coli BR513 was measurable at about 10 times the MIC, though no induction occurred at 20 micrograms of nalidixic or oxolinic acid per ml. Genotoxicity of quinolones also was observed in the Bacillus subtilis DNA repair assay, in which the mutant strain M45 (recA) was more susceptible to quinolones than its parent strain, H17 (rec+). The results from these analyses indicate that quinolones induce SOS functions and are mutagenic in bacteria; these properties correspond to their antimicrobial activities.